2012
DOI: 10.1186/1472-6882-12-60
|View full text |Cite|
|
Sign up to set email alerts
|

Role of quercetin and arginine in ameliorating nano zinc oxide-induced nephrotoxicity in rats

Abstract: BackgroundNanoparticles are small-scale substances (<100 nm) with unique properties. Therefore, nanoparticles pose complex health risk implications. The objective of this study was to detect whether treatment with quercetin (Qur) and/or arginine (Arg) ameliorated nephrotoxicity induced by two different doses of nano zinc oxide (n-ZnO) particles.MethodZnO nanoparticles were administered orally in two doses (either 600 mg or 1 g/Kg body weight/day for 5 conscutive days) to Wister albino rats. In order to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 63 publications
7
38
1
Order By: Relevance
“…However, some studies indicated that rat CRP is used for the marker of inflammation (2,12,18). In this study it was determined that CRP concentrations were raised after administrations in three group but this increase was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies indicated that rat CRP is used for the marker of inflammation (2,12,18). In this study it was determined that CRP concentrations were raised after administrations in three group but this increase was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…CRP, is reported as major acute phase protein in human and canine (4,10,15). CRP is a useful marker of inflammatory clinical situation (12). In the rat CRP has been studied as a marker of inflammation using experimental models (2,12,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small particle size of NPs including ZnO-NPs creates large surface area per unit mass, thus increasing surface reactivity of NPs in the cells and their ability to produce reactive oxygen species (ROS) [13]. Therefore, NPs may cause more inflammation than larger particles of the same materials at the same dose [60].…”
Section: Introductionmentioning
confidence: 99%
“…NPs can enter the human body through different routes as ingestion and inhalation [13]. Due to their small size, NPs can translocate through epithelial and endothelial cells into the circulatory and lymphatic systems to reach body tissues and organs as liver, kidneys, heart, spleen and bone marrow where they induce cell damage by oxidative stress and/or organelle injury [2,45,61].…”
Section: Introductionmentioning
confidence: 99%